Spinal tuberculosis: Our experience and a review of imaging methods. Issue 5 (October 2015) - Rauf, Fareeha; Chaudhry, Umair Rashid; Atif, Mohammad; ur Rahaman, Mujib
We share our experience of 2000 spinal tuberculosis (TB) cases, including both typical and atypical presentations. The aim of the study is to estimate the incidence and types of spinal TB referred to our department for diagnosis. 2000 patients were selected by convenience sampling from January 2006 to September 2010. Study design was descriptive and among 2000 mostly unknown cases without evidence of symptoms of systemic TB (1080 males and 920 females). MRI without and with IV contrast, CECT with MPR, and in some cases not fit for MRI, CT myelography, were performed. Out of 2000 cases of tuberculous spine, 1080 (54%) were male and 920 (46%) were female. Their age ranged from 8–60 years. About 90% of patients were below the age of 40 years. Peak age among the males and females was 20–29 years and 14–35 years, respectively. The most common site of involvement was dorsal spine (45%) followed by lumbo-sacral spine (33%), cervical spine (10%) and at multiple levels (12%). Biopsies were done in 240 (12%) cases. Spinal TB should always be suspected when radiographs demonstrate a destructive spinal process. Awareness and prompt management of TB spine will help in reducing the continuing morbidity of this disease.